New Firm Survival: New Results Using a Hazard Function - Audretsch, David B.; Mahmood, Talat (The Review of Economics and Statistics, 1995)
A limitation of Audretsch's 1991 study of new-firm survival was the level of aggregation to industries. This precluded linking establishment-specific characteristics, such as organizational structure and size, to post-entry performance. The purpose of this paper is to relate the post-entry performance of individual establishments not only to their technological and market structure environments, but also to establishment-specific characteristics. We do this by estimating a hazard duration function for more than 12, 000 individual establishments in U.S. manufacturing started in 1976 by tracking their subsequent performance over a ten-year period. We conclude that establishment-specific characteristics, which Audretsch was not able to capture in his earlier study, play an important role in shaping the exposure to risk confronting new establishments. Copyright 1995 by MIT Press.